The Effectivity of Solid Medical Waste Management in Pandemic Era - Abidah, Hilda Nur; Ismah, Hashifah Azatil; Irmayanti, Selvi; Nurika, Globila; Wikurendra, Edza Aria (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: The increasing of confirmed positive case of SARS-Cov-2 Virus impacts to the need for improvement of health services, especially to the health workers and medical equipment. Along with the importance of regarding need of health service, it causes the rise number of medical waste that leads to health problem crisis. Therefore, this article presents common insight of the effectivity and challenge of medical waste management in Covid-19 pandemic.Methods: The notion is gained by finding out the source database from Pubmed, ScienceDirect, Google scholar, Researchgate that classified based on the research purpose. The keywords used were: (1) Covid-19 and medical waste; (2) pandemic solid waste; (3) waste and Covid-19; (4) management and pandemics.Results: An effective method to be applied is sterilizer technology, such as VH2O2 dan Stryker STERIZONE VP4, and the development of late waste respirator with the pyrolysis process. The method and the management process is considered, either nationally or internationally, as effective, but still we found challenge to implement the method, as lack of socialisation and support from the functionary.  Conclusion: the method management can be implemented in the various countries, based on the needs and capability.